Tinjauan Hukum Islam terhadap Pelaksanaan Akad Murabahah di Koperasi Amanah Mulia Ikhlas Pinrang: An Analysis of Murabahah Contract Practices at Koperasi Amanah Mulia Ikhlas Pinrang from the Perspective of Islamic Law - Munira, Munira; Akhmad Hanafi Dain Yunta; Humairah Ahsan (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2025)
Murabahah contracts are one of the most widely applied forms of sale and purchase in Islamic financial institutions because they are considered transparent in pricing and in accordance with sharia principles. However, in practice, a number of challenges are still found, such as inconsistencies between practice and fiqh principles, limited understanding among customers, and the potential for practices resembling usury. This study aims to examine the mechanism of murabahah contract implementation at Koperasi Amanah Mulia Ikhlas Pinrang and to assess its validity from the perspective of Islamic law. The research employs a qualitative approach with a field research design. Data were collected through direct interviews with cooperative administrators and documentation studies related to the murabahah contracts carried out. The data analysis was conducted descriptively and analytically using a juridical-normative approach, supported by classical and contemporary fiqh muamalah literature from various schools of thought. The findings show that the implementation mechanism of murabahah contracts at Koperasi Amanah Mulia Ikhlas is carried out through two main stages, namely the financing application stage and the contract execution stage. In general, the practice of the contract has fulfilled the pillars and conditions of murabahah as established in Islamic jurisprudence, although there are still some aspects that need improvement, particularly in documentation and in members’ understanding of their rights and obligations. This research provides important implications for Islamic cooperatives in optimizing the comprehensive and consistent application of sharia principles in murabahah financing contracts.